Love in colour - Babalola, Bolu (2020)
Discover love from times long ago... Join Bolu Babalola as she retells the most beautiful love stories from history and mythology in this stunning collection. From the homoromantic Greek myths, to magical Nigerian folktales, to the ancient stories of South Asia, Bolu brings new life to tales that truly show the vibrance and colours of love around the world. The anthology is a step towards decolonising tropes of love, and celebrates in the wildly beautiful and astonishingly diverse tales of romance and desire that already exist in so many cultures and communities. Get lost in these mystical worlds and you will soon realise that humanity - like love - comes in technicolour.
Keywords: Romance fiction, English; Folklore